Ebola virus disease 2014 - Galán Huerta, Kame Alberto; Arellanos Soto, Daniel; Rivas Estilla, Ana María; Bravo de la Cruz, Verónica; Ramos Jiménez, Javier (UANL. Facultad de Medicina, 2014)
Ebola virus disease was irst described in 1976 originating from the Ebola River in the Democratic Republic of Congo. Since then, Ebola virus has become an important public health threat in Africa, and now it is of great concern worldwide due to the recent outbreaks (9216 cases with 4555 deaths up to October 20th, 2014), and it is so far the largest and deadliest recorded in history. Five Ebola virus species have been identiied (including Zaire, Sudan, Ivory Coast, Reston, and Bundibugyo Ebola virus), and four of them have proved to be highly pathogenic for both human and non-human primates, causing viral hemorrhagic fever with case fatality rates of up to 90%, for which no approved therapeutics or vaccines are currently available. Ebola virus infections are characterized by immune suppression and a systemic inlammatory response that causes impairment of the vascular, coagulation, and immune systems, leading to multiorgan failure and shock, and thus, in some ways, resembling septic shock. The major affected countries, Sierra Leone, Guinea, Liberia, and Nigeria, have been struggling to contain and to mitigate the outbreak. Gene sequencing of the 2014 virus (2014WA) outbreak has demonstrated 98% homology with the Zaire Ebola virus, with a 49% case fatality ratio across the affected countries. In this review the characteristics of the viruses, pathogenesis, diagnosis, treatment, and the cases reported in health care workers (HCW) are described, as well as a summary of outbreaks of the virus since its discovery, including these last two outbreaks in Africa.